2011
DOI: 10.3174/ajnr.a2518
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral CT Perfusion Using an Interventional C-Arm Imaging System: Cerebral Blood Flow Measurements

Abstract: BACKGROUND AND PURPOSE CTP imaging in the interventional suite could reduce delays to the start of image-guided interventions and help determine the treatment progress and end point. However, C-arms rotate slower than clinical CT scanners, making CTP challenging. We developed a cerebral CTP protocol for C-arm CBCT and evaluated it in an animal study. MATERIALS AND METHODS Five anesthetized swine were imaged by using C-arm CBCT and conventional CT. The C-arm rotates in 4.3 seconds plus a 1.25-second turnaroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 19 publications
0
65
0
1
Order By: Relevance
“…27 Moreover, our focus was to find out whether assessment of dynamic perfusion parameters was feasible in a new large-animal model. However, quantification is possible as was demonstrated by Ganguly et al 13 They stated that CBF measured with C-arm cone beam CT correlated well with that from CTP, but in this work, multiple injections and multiple acquisitions were performed to overcome the temporal resolution limits of the C-arm system, whereas we chose a protocol with a single injection and only 1 fill run. Third, we chose sheep for our experiments because the technique of surgical occlusion was described and sheep have a larger, gyrencephalic brain, as opposed to that in most other animal stroke models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 Moreover, our focus was to find out whether assessment of dynamic perfusion parameters was feasible in a new large-animal model. However, quantification is possible as was demonstrated by Ganguly et al 13 They stated that CBF measured with C-arm cone beam CT correlated well with that from CTP, but in this work, multiple injections and multiple acquisitions were performed to overcome the temporal resolution limits of the C-arm system, whereas we chose a protocol with a single injection and only 1 fill run. Third, we chose sheep for our experiments because the technique of surgical occlusion was described and sheep have a larger, gyrencephalic brain, as opposed to that in most other animal stroke models.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental and clinical studies have demonstrated that measurement of CBV is feasible by using C-arm CT. [10][11][12] More recently, CBF was measured in healthy swine and canines with such a system. 13,14 We report our experience using a modified C-arm system to measure steady-state CBV and also to make dynamic measurements of CBF in an experimental sheep stroke model.…”
mentioning
confidence: 99%
“…However, recent studies in canines and swine models have now demonstrated the feasibility of dynamic perfusion imaging with the use of a flat detector angiographic system. [10][11][12] The aim of this pilot study was to test the feasibility of this novel application by comparing FD-CTP and FD-CTA with a multimodal MR imaging protocol in patients with acute ischemic stroke. Additionally, the effective patient dose was evaluated.…”
mentioning
confidence: 99%
“…11 Briefly, before the start of the contrast injection, 1 forward and 1 reverse highspeed baseline scan (rotation) were performed to obtain a baseline set of nonenhanced (mask) images. Five seconds after the start of the peripheral contrast injection, a bidirectional series of 7 high-speed FD-CT rotational acquisitions was initiated.…”
mentioning
confidence: 99%
See 1 more Smart Citation